UPAYA PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA MELALUI MODEL ACTIVE LEARNING TIPE ROLE REVERSAL QUESTION PADA SISWA KELAS VIII A SMPN 21 MATARAM - Vitha Megarivera; M. Ismail; Bagdawansyah Alqadri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the improvement in civic education learning outcomesthrough the implementation of Active Learning model of the Role ReversalQuestion type among Class VIII A students at SMPN 21 Mataram. The researchemployed a classroom action research design. The subjects of the study were 32students of Class VIII A. Data collection methods included test, observation, anddocumentation. The instruments used were tests and observation sheets. Datawere analyzed using both quantitative and qualitative descriptive techniques. Thesuccess indicator of the action was set at ≥75% of students achieving a minimumscore of 75. The results showed an improvement in Civic Education learningoutcomes after applying the Active Learning model of the Role Reversal Questiontype in both Cycle I and Cycle II. In Cycle I, 37.5% of students scored ≥75, whichincreased by 56.25% to 93.75% in Cycle II. The average student score alsoincreased from 72.53 in Cycle I to 82.62 in Cycle II, reflecting an improvement of10.09 points. These findings indicate that the Role Reversal Question type ofActive Learning is effective in enhancing students Civic Education learningoutcomes.